2017
DOI: 10.1055/s-0043-107881
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Authenticity of Herbal Dietary Supplements: Comparison of Chemical and DNA Barcoding Methods

Abstract: About 7 % of the U. S. population reports using botanical dietary supplements. Increased use of such supplements has led to discussions related to their authenticity and quality. Reports of adulteration with substandard materials or pharmaceuticals are of concern because such substitutions, whether inadvertent or deliberate, may reduce the efficacy of specific botanicals or lead to adverse events. Methods for verifying the identity of botanicals include macroscopic and microscopic examinations, chemical analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 34 publications
0
50
0
Order By: Relevance
“…This shows the boundedness of DNA barcoding due to the instability of DNA. This result also reflects the limitations of Sanger sequencing, such as the unspecific amplification of non-target DNA when target DNA is degraded (Pawar et al, 2017). In the method part, we have taken some measures to avoid these problems.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…This shows the boundedness of DNA barcoding due to the instability of DNA. This result also reflects the limitations of Sanger sequencing, such as the unspecific amplification of non-target DNA when target DNA is degraded (Pawar et al, 2017). In the method part, we have taken some measures to avoid these problems.…”
Section: Resultsmentioning
confidence: 97%
“…If mixed sequencing signals were present, we would clone the PCR products and sequence the single colonies to identify target amplicons. To overcome the limitations of Sanger sequencing, we can employ next-generation sequencing (NGS) approach technology to simultaneously detect plant and fungal DNAs (Pawar et al, 2017). And it is also possible that the samples were not suitable for ITS2 or psbA-trnH amplification.…”
Section: Resultsmentioning
confidence: 99%
“…A global analysis of nearly 6,000 herbal products sold in 37 countries has revealed that 27% of the products contain undeclared contaminants, substitutes, or filler species (Ichim, 2019). To address this problem, DNA barcoding as powerful strategy has recently attracted considerable attention and, along with chemical methods (de Boer et al, 2015;Pawar et al, 2017;Sgamma et al, 2017), has started to enter the regulatory systems for quality control (Pharmacopoeia Committee of P. R. China, 2015; British Pharmacopoeia Commission, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…While macroscopic and microscopic examinations are easily applied to fresh whole plants or plant parts, dried products, as those typically sold on the market, are generally difficult to identify, as many useful diagnostic characteristics are lost during dehydration (Joharchi and Amiri, 2012). In addition, often macroscopic or microscopic examinations will fail because a preparation consists of multi-component powdered samples that have been processed beyond the extent that would allow morphological characterizations (Pawar et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies address the particularity of DNA barcoding as an accessory tool in the identification of plants (Pawar et al 2017;Palhares et al 2015;International Organization for Standardization [ISO] 2017;Sgamma et al 2017). However, to the best of our knowledge, few studies report an effective joint effort of forensic chemistry and forensic botany techniques and the problem of its practical forensic application or describe a real case solved in a forensic laboratory with its difficulties and limitations.…”
mentioning
confidence: 99%